The Use of Japanese Adjectives Ureshii and Tanoshii - Hamzah, Nor Sahayu; Mohd Zin, Zaid; Che Rodi, Rozita (Issues in Language Studies, 2020)
This study is a semantic study that explores the genre of meaning in general. It focuses on the synonyms of adjectives ureshii and tanoshii in the construction of sentences in the Japanese language. The objective of this study is to discuss similarities and differences of the usage of synonyms ureshii and tanoshii and also to analyse the implementation from the perspective of adjectives in the Malay language. The data selected for this study are sentences that contained ureshii and tanoshii lexicons based on Shinmeikai Japanese Language Dictionary (2012). This study utilizes qualitative research methodology in which the data are analysed descriptively. Besides that, the data are also analysed using textual analysis based on the conceptual framework by Ibrahim Ahmad (2005). The findings of this study elucidate the technical differences in the usage of Japanese adjectives ureshii and tanoshii as compared to Malay adjectives gembira [happy] and seronok [excited]. It shows that the two adjectives have similar meaning and nuance but cannot be used interchangeably. The outcomes of this study can be used as reference material for teachers and students to master the usage of adjectives in Japanese language. Lastly, further studies on Japanese lexicon keiyoushi should be carried out entirely.